2012
DOI: 10.1159/000335915
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Deficits and Cognitive Dysfunction in Parkinson’s Disease

Abstract: Background: Olfactory deficits and executive dysfunction have been reported in Parkinson’s disease (PD). However, the association between these deficits has not been thoroughly examined. Methods: We studied 44 PD subjects and 17 age-matched controls. In PD subjects, symptoms were assessed with the Unified Parkinson’s Disease Rating Scale and the Hoehn and Yahr scale. Cognition in both groups was assessed by a neuropsychological battery. Olfactory identification and sensitivity was evaluated with the Sniffin’ S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Therefore, our transgenic mouse model with late Thy1-A30P α-SYN expression reflects, in part, the pathology observed in brains of PD patients with Lewy bodies in MCs of the OB78, the human olfactory deficit at an early stage of the disease process123 and a lack of progenitor cells10. Importantly, our results support the previously reported association between adult neurogenesis and fine odour discrimination495758; although we still lack the molecular and cellular mechanism to explain olfactory deficits in these mice59.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, our transgenic mouse model with late Thy1-A30P α-SYN expression reflects, in part, the pathology observed in brains of PD patients with Lewy bodies in MCs of the OB78, the human olfactory deficit at an early stage of the disease process123 and a lack of progenitor cells10. Importantly, our results support the previously reported association between adult neurogenesis and fine odour discrimination495758; although we still lack the molecular and cellular mechanism to explain olfactory deficits in these mice59.…”
Section: Discussionmentioning
confidence: 94%
“…Hyposmia is one of the most frequent non-motor symptoms of Parkinson disease (PD)123, being detected in the majority of PD patients several years before the first appearance of motor symptoms4. Moreover, deposition of fibrillar α-synuclein (α-SYN) aggregates56 - the main pathological hallmark of the disease - occurs inside olfactory bulb (OB) neurons of PD patients78.…”
mentioning
confidence: 99%
“…Similarly, Haehner et al () showed that patients with Parkinson's disease with an impairment of verbal fluency improved after OT. Also, Parrao et al () assumed a close association between cognitive function and olfactory function in Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be hypothesized that this specific effect on odor discrimination relates to the interaction between cognitive and olfactory function. Recent research by Damholdt et al (2011) and Parrao et al (2012) suggested that there is a close association between cognitive function and olfactory function in PD patients. This might be a further hint to the beneficial effect of rasagiline on human cognition, which was recently described by Hanagasi et al (2011).…”
Section: Discussionmentioning
confidence: 99%